Analisis Column Settling Air Permukaan yang Dikoagulasi dengan Biokoagulan Biji Pepaya: Analysis of Column Settling Surface of Water Coagulated with Biocoagulant Papaya Seed - Lita Darmayanti; Hamdani Hamdani; Shinta Elystia (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Water of river has high turbidity so it needs to be treated before being used as clean water. Common processing is coagulation, flocculation, sedimentation, and filtration. Type II sedimentation is the settling of flokulen particles, where there is an interparticle interaction so that the size increases and the rate of settling increases. This study aims to analyze the settling column in order to get isoremoval graphs of river water that have been coagulated using papaya seed biocoagulants. Isoremoval graph is useful for determining the value of surface loading rate (Vo) and time of detention (td) making it easier to design sedimentation tank. The study was conducted using a settling column with a diameter of 12.5 cm with a height of 150 cm. The operating conditions varied are sampling point depth of 25 cm, 50 cm, 75 cm, 100 cm and 125 cm with sampling time per port 10 minutes, 20 minutes, 30 minutes, 45 minutes and 60 minutes. The results showed the best turbidity of the settling column was 88.81% at a column settling depth of 25 cm with settling time of 60 minutes. The surface loading rate obtained to produce 85% deposition is 55 m3day-1m-2 with a detention time of 40 minutes.